ANALISIS PENERIMAAN PESERTA DIDIK BARU BERBASIS ZONASI DI INDONESIA - Risa Tantri; Ismira (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
PPDB (New Student Admission) Zoning is a system used in accepting new students in schools in Indonesia. There are several problems that occur in implementing PPBD, including unclear zoning, unequal facilities, data manipulation, scarce school places, a system that is not transparent, lack of communication, limited facilities and high competition. In this article, the researcher explains the problems regarding the implementation of PPDB and the author also provides solutions to these problems. There are several solutions that the author puts forward in overcoming the problems that exist in implementing the school zoning system in zoning-based PPDB. It is necessary to make improvements or suggest improvements. And the author presents the flow of educational philosophy and educational policy which is not always direct or exclusive. Most educational systems combine elements from several philosophical schools such as perennialism, essentialism, pragmaticism, progressivism.